SHOULD WE ALL SAVE OURSELVES FROM COXSACKIE?! OR FEAR MAKES THE WOLF BIGGER THAN HE IS - Zalina A. Alacheva; Olga B. Rybalka; Tatyana V. Kulichenko (Вопросы современной педиатрии, 2017)
Every year, an increase in the incidence of enterovirus infection is registered everywhere, including Coxsackie viruses. Parents of sick children are often very uneasy considering these viruses to be extremely dangerous and the disease to be severe one, with possible adverse consequences.  The situation is exacerbated  by many mass media that inform about the epidemic of Coxsackie virus, which causes  a terrible  disease.  The article gives main characteristics  of microorganisms,  modes  of infection,  clinical manifestations  of enterovirus infections as well as measures for prevention and treatment.